Positron Emission Tomography–Adapted Therapy in Bulky Stage I/II Classic Hodgkin Lymphoma: CALGB 50801 (Alliance). Issue 5 (10th February 2023) - LaCasce, Ann S.; Dockter, Travis; Ruppert, Amy S.; Kostakoglu, Lale; Schöder, Heiko; Hsi, Eric; Bogart, Jeffrey; Cheson, Bruce; Wagner-Johnston, Nina; Abramson, Jeremy; Blum, Kristie; Leonard, John P.; et al.
Abstract : PURPOSE: Patients with bulky stage I/II classic Hodgkin lymphoma (cHL) are typically treated with chemotherapy followed by radiation. Late effects associated with radiotherapy include increased risk of second cancer and cardiovascular disease. We tested a positron emission tomography (PET)–adapted approach in patients with bulky, early-stage cHL, omitting radiotherapy in patients with interim PET-negative (PET−) disease and intensifying treatment in patients with PET-positive (PET+) disease. METHODS: Eligible patients with bulky disease (mass > 10 cm or 1/3 the maximum intrathoracic diameter on chest x-ray) received two cycles of doxorubicin, bleomycin, vinblastine, and dacarbazine (ABVD) followed by interim fluorodeoxyglucose PET (PET2). Patients with PET2–, defined as 1-3 on the 5-point scale, received four additional cycles of doxorubicin, bleomycin, vinblastine, and dacarbazine. Patients with PET2+ received four cycles of escalated bleomycin, etoposide, doxorubicin, cyclophosphamide, vincristine, procarbazine, and prednisone followed by 30.6 Gy involved-field radiation. RESULTS: Of 94 evaluable patients, 53% were female with median age 30 years (range, 18-58 years). Eight-five (90%) had stage II disease, including 48 (51%) with stage IIB/IIBE. Seventy-eight (78%) were PET2– and 21 (22%) were PET2+. The predominant toxicity was neutropenia, with 9% of patients developing febrile neutropenia and one developing sepsis. The primary end point of 3-year progression-free survival (PFS) was 93.1% in PET2– and 89.7% in PET2+ patients. Three-year overall survival was 98.6% and 94.4%, respectively. The estimated hazard ratio comparing PFS of patients with PET2+ and patients with PET2− was 1.03 (85% upper bound 2.38) and was significantly less than the null hypothesis of 4.1 (one-sided P = .04). CONCLUSION: Our study of PET-adapted therapy in bulky stage I/II cHL met its primary goal and was associated with an excellent 3-year PFS rate of 92.3% in all patients, with the majority being spared radiotherapy and exposure to intensified chemotherapy.